Implementasi Program Indonesia Pintar di Sekolah Dasar Negeri 1 Kolakaasi Kabupaten Kolaka - Yudi Agusman (Universitas Warmadewa, 2019)
Abstract This study aims to determine and describe the implementation of the Smart Indonesia Program (PIP) in SD Negeri 1 Kolakaasi, Kolaka Regency. This research uses a descriptive qualitative approach. Research informants were selected by purposive sampling. Data collection techniques used were interviews, observation, and study of literature. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawing with the focus of this research directed towards standards and policy objectives, resources, communication between institutions and activity consulidation, characteristics of implementing agencies, conditions social, economic and political, and implementor disposition. The results showed that from the variable size and policy objectives, it had not been fully achieved, because there were still poor students who had not received PIP. Human resources are in accordance with the requirements required, funding resources are experiencing delays in PIP fund disbursement, and there are problems in the distribution of PIP funds and the lack of optimal oversight of funds for beneficiaries. The characteristics of the implementing agent in carrying out their duties have tried to carry out their responsibilities based on the established rules. Disposition of the implementers of the PIP recipients was very enthusiastic and mixed well with the parents of students, communication between institutions and the consolidation of activities in socializing PIP has not been fully realized in doing so and social conditions, as well as the support and participation of parents is quite good, the economic conditions are low and political elites at the village, school and education offices support the success of this program. Keywords: Implementation; the smart indonesia program; primary school Abstrak Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan implementasi Program Indonesia Pintar (PIP) di SD Negeri 1 Kolakaasi Kabupaten Kolaka. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Informan penelitian dipilih secara purposive sampling. Teknik pengumpulan data yang digunakan adalah wawancara, pengamatan, dan studi literature. Teknik analisis data yaitu pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan dengan fokus penelitian ini diarahkan mengenai standar dan sasaran kebijakan, sumber daya, komuniksai antar instusi dan konsulidasi aktifitas, karakteristik agen pelaksana, kondisi sosial, ekonomi dan politik dan disposisi implementor. Hasil penelitian menunjukkan dari variabel ukuran dan tujuan kebijakan, belum sepenuhnya tercapai, karena masih ada siswa miskin belum menerima PIP. Sumber daya manusia sudah sesuai dengan syarat yang dibutuhkan, sumber daya dana mengalami keterlambatan pencairan dana PIP, dan ada masalah dalam pendistribusian dana PIP serta belum optimalnya pengawasan dana bagi penerima manfaat. Karakteristik agen pelaksana dalam menjalankan tugasnya sudah berusaha melaksanakan tanggung jawabnya berdasarkan praturan yang sudah ditetapkan. Disposisi implementor para pelaksana penerima PIP sangat antusias dan berbaur baik dengan orang tua siswa, komunikasi antar insitusi dan konsilidasi aktivitas dalam mensosialisasikan PIP belum sepenuhnya terealisasi dalam melakukannya dan kondisi sosial, serta adanya dukungan dan partisipasi dari orang tua cukup baik, kondisi ekonomi yang rendah dan elite politik ditingkat kelurahan, sekolah maupun Dinas Pendidikan mendukung keberhasilan program ini. Kata Kunci: Implemetasi; program indonesia pintar; sekolah dasar